Homoeopathy Modulates Lipid Metabolism – Recent Researches (Homoeopathy for All, 2023)
Cases of hyperlipidaemia have been  increasing in recent years. Current  urban lifestyle, including food  habits, is to be blamed. A compilation  of homoeopathic drugs useful in the  management of high lipid profile  published erstwhile is a good tool  for clinical practice1. That article  was based on the studies conducted  using those herbs in crude or as  extract, etc. This article highlights  a few such studies which have been  conducted using homoeopathic  drugs.
Keywords: hyperlipidaemia; management